Impact of population screening for Lynch syndrome insights from the All of Us data - Jiheum Park; Hemanth Karnati; Sheila D. Rustgi; Chin Hur; Xiao-Fei Kong; Fay Kastrinos (Nature Communications)
Abstract Lynch Syndrome (LS) is a common genetic cancer condition that allows for personalized cancer prevention and early cancer detection in identified gene carriers. We used data from the All of Us (AOU) Research Initiative to assess the prevalence of LS in the general U.S. population, and analyzed demographic, personal, and family cancer history, stratified by LS genotype to compare LS and non-LS carriers. The results suggest that population-based germline testing for LS may identify up to 63.2% of carriers who might remain undetected due to lack of personal or family cancer history. LS affects about 1 in 354 individuals in this U.S. cohort, where pathogenic variants in the genes MSH6 and PMS2 account for the majority of cases. These results underscore the need to optimize the identification of LS across diverse populations and population-based germline testing may capture the most individuals who can benefit from precision cancer screening and prevention.